2020
DOI: 10.18231/2454-6712.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

A study of dog bites among children in the rural area of Goa, India

Abstract: Objective: 1. To study the prevalence of dog bites in children; 2. To study knowledge and practices followed regarding prevention and control of rabies among caretakers. Materials and Methods: Study Design: Cross sectional study; Study Participants: Children below 16 years of age; Study Instrument: A predesigned questionnaire was used to ask questions to parents or caretakers of children. Ethical Considerations: Ethical approval was obtained from Institutional Ethics Committee. Statistical Analysis: Data was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…29,31,34,42 Another study reported a dog bite incidence of 1.03%, 8.66% and 1.7% in the age groups of 0-5, 6-10 and 11-16 years respectively in rural parts of Goa in 2018. 39 Sex: The males in the reported studies have disproportionately experienced more dog bites than females. The studies reported the dog bites in males in a range of 57.1%-80.2%.…”
Section: Socio-demographics Of Dog-bite Victimsmentioning
confidence: 96%
See 4 more Smart Citations
“…29,31,34,42 Another study reported a dog bite incidence of 1.03%, 8.66% and 1.7% in the age groups of 0-5, 6-10 and 11-16 years respectively in rural parts of Goa in 2018. 39 Sex: The males in the reported studies have disproportionately experienced more dog bites than females. The studies reported the dog bites in males in a range of 57.1%-80.2%.…”
Section: Socio-demographics Of Dog-bite Victimsmentioning
confidence: 96%
“…Only one modeling study reported all the three outcomes: epidemiological, economic and humanistic. 1 Out of 35 included studies, 23 were hospital (or clinic) based, [20][21][22][24][25][26][27][28][29][30][31]38,41,42,[44][45][46][47][48][49][50][51][52] 9 were community (or household) based 4,23,[32][33][34][35]37,39,40 and 2 were modeling studies at country level 1,43 and was laboratory-based study. 36…”
Section: Search and Screeningmentioning
confidence: 99%
See 3 more Smart Citations